Phytoremediation of Cr(VI) and Pd(II) using vetiver grass (Chrysopogon Zizanioides) - Chirwa, Evans M.N. (University of Pretoria, 2022)
Dissertation (MEng (Chemical Engineering))--University of Pretoria, 2022.